Investigation Of Submicron Particles Incorporate In Silane To Improve Hydrophobicity With The Potential Application In Batik Industry - Endut, Noor Suhaiza Che (Universiti Sains Malaysia, 2017)
Hydrophobic coatings are widely used in automotive, electronic, medical, paint coating, textiles and many other industries. The main focus of this work is to improve hydrophobicity by incorporate nanoparticle into silane to satisfy both hydrophobic surface requirements which are rough surface and low surface energy. In this work, zinc oxide (ZnO) particle was incorporate in Polydimethylsiloxane (PDMS) which used as the hydrophobic precursor due to its properties of non-fluorinated and low surface energy material. The ZnO particles were deposited on cloth substrate by dip-coating method. The effect of ZnO particles amount and different morphology on wettability has shown that ZnO flake particles with composition of 0.10 g have improved the WCA up to 144º. Various research has been directed in several decades towards the creation of water repellent textiles. However, application of hydrophobic barrier to replace paraffin wax in batik making has not been explored yet. Silica solution (SS) which extracted from oil palm ash were added into PDMS/ZnO hydrophobic solution to formulate solution that have similar properties to paraffin wax. 30PZF:70SS is best composition of PDMS/ZnO/SS which has exhibit WCA up to 146º and demonstrated good hydrophobic barrier by resisting dye penetration. Therefore, in this project, application of hydrophobic to replace paraffin wax was successfully fabricated and exhibit WCA nearest to exhibit super-hydrophobic (>150º). Simple method to remove the hydrophobic also achieved by immersed the hydrophobic coating into buffer solution with pH 4 and 10 for 48 hours also discovered.